2016
DOI: 10.1089/ther.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Time to Cooling Is Associated with Resuscitation Outcomes

Abstract: Our purpose was to analyze evidence related to timing of cooling from studies of targeted temperature management (TTM) after return of spontaneous circulation (ROSC) after cardiac arrest and to recommend directions for future therapy optimization. We conducted a preliminary review of studies of both animals and patients treated with post-ROSC TTM and hypothesized that a more rapid cooling strategy in the absence of volume-adding cold infusions would provide improved outcomes in comparison with slower cooling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…The authors reported that age, shockable initial rhythm, time in cardiac arrest and induction time > 300 min were associated with a higher probability of a favorable neurologic outcome. In contrast to this, other publications showed rapid TT achievement to be associated with better neurologic results [20][21][22][23]. However, all those studies defined time to TT as the period from the onset of cardiac arrest to arrival at a temperature of 33°C or < 34°C, therefore it was equivalent to three different time intervals used in the current study (time in cardiac arrest, pre-induction and induction).…”
Section: Discussionmentioning
confidence: 90%
“…The authors reported that age, shockable initial rhythm, time in cardiac arrest and induction time > 300 min were associated with a higher probability of a favorable neurologic outcome. In contrast to this, other publications showed rapid TT achievement to be associated with better neurologic results [20][21][22][23]. However, all those studies defined time to TT as the period from the onset of cardiac arrest to arrival at a temperature of 33°C or < 34°C, therefore it was equivalent to three different time intervals used in the current study (time in cardiac arrest, pre-induction and induction).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, CRRT cooling might be a safe way to induce TH with high e ciency. Additionally, a review [19] demonstrated that the achievement of temperature below 34℃ within 3.5 h after ROSC seemed to be bene cial. In the present study, the blood temperature was initially decreased rapidly by submerging the circuit in ice water to release heat, followed by the maintenance of TH by wrapping the circuit within an adjustable heating device.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite TH has been proved to exert potent protection for CA survivors [14,15], more than 50% of them die or have poor neurological outcome [16][17][18]. A review demonstrated that rapid cooling exerted a higher rate of good neurological outcome than slower cooling methods [19]. A cooling rate of > 3℃/h appear to be bene cial to arrive at a targeted temperature below 34℃ within 3.5 h after return of spontaneous circulation (ROSC) [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized trials have not shown improvement of outcomes with prehospital initiation of therapeutic hypothermia 46,47 . One trial demonstrated worse outcomes in those arriving at goal temperature rapidly while others have demonstrated improved outcomes 48–50 . Unfortunately, none of these trials have stratified enrollment based on initial neurologic injury, limiting the use of their results.…”
Section: Determining the Etiologymentioning
confidence: 99%